Is Efficiency the Equivalent to a High Rate of Return for Private Pension Funds? Evidence from Latin American Countries - Guillen, Jorge B. (2008)
During the last few years, there has been a large increase in the rate of return for most Latin American private pension fund institutions (AFPs). This favorable performance of funds comes with an economic boom in the region. However, efficiency, which is the equivalent of good management, does not go along with this successful performance of AFPs. We measure efficiency with the Data Envelopment Analysis technique, and we test for a sample of 9 countries in Latin America to determine if there is any link between efficiency of AFPs and their rate of return. The results suggest that local market power is not necessarily sufficient for certain large AFPs.